REASONS BEHIND THE USAGE OF ONLINE AD BLOCKING TOOLS - Kuukkanen, Tatu (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Online advertising has been growing rapidly since the mid-90s. In recent years, online advertising has become as relevant as an advertising medium as print and television are. However, despite the growth, the generally held consensus is that consumers are not interested in online advertisements. The arrival of online ad blocking tools has offered consumers a very effective way to avoid and block online advertisements. Although these tools have now been around for several years and the most popular software’s have hundreds of millions of active users, the phenomenon of ad blocking has gathered surprisingly little attention from academic marketing research. For this reason, ad blocking was chosen as the topic of this thesis study. The researcher was particularly interested in the reasons behind the usage of online ad blocking tools. The object of the empirical part of this study is to provide new and valid information regarding the reasons behind the usage of online ad blocking tools. The empirical research of this study consisted of a survey study that mixed both quantitative and qualitative elements. Although the sample size of the study was fairly limited, the study provided useful answers to individual research questions and provided new knowledge regarding the reasons behind the usage of online ad blocking and the phenomenon of ad blocking as a whole. The study provides further evidence that consumers are aware of online ad blocking tools and a significant portion of them are interested in using them. This study indicates that many of the consumers who do not have previous knowledge of these tools would actually be interested in them. The reason for the usage of online ad blocking tools varies from institutional reasons to instrumental reason, such as poor quality of the online advertisements. However, there were participants who were not interested in the usage of online ad blocking tools, and some of them reported to find online advertising useful. There also seems to be a concern among some consumers that online ad blocking will have a negative effect on online content in the future if the ad blocking will keep growing as a phenomenon. This certainly can be the case, and it is very interesting to see how the development of online ad blocking will shape the online advertising, how the advertising industry will respond to the growth of online ad blocking and how will the consumers respond to these changes.

Verkkomainonnan merkitys mediamainonnalle on kasvanut huomattavasti lähivuosien aikana. Tutkimukset osoittavat, että vahvasta kasvusta huolimatta, kuluttajat eivät kuitenkaan ole kiinnostuneita verkkomainonnasta. Verkkomainosten esto-ohjelmista onkin tullut kuluttajille suosittu tapa suodattaa ja estää verkossa esitettävät mainokset. Vaikka verkkomainosten estoohjelmia on ollut saatavilla jo useiden vuosien aikana ja niiden käyttäjämäärät ovat merkittävät, verkkomainosten esto-ohjelmia on tutkittu hyvin vähän akateemisesti. Tämän vuoksi verkkomainosten estäminen on valittu tämän tutkielman aihealueeksi. Tutkija on etenkin kiinnostunut kuluttajien asenteista verkkomainosten esto-ohjelmia kohtaan ja syistä ohjelmien käyttöön. Tutkimuksen empiirisen osion tarkoituksena on tuottaa uutta tietoa juuri näistä asenteista ja käyttöön johtavista syistä. Tutkielman empiirinen osa koostui kyselytutkimuksesta, jossa sovellettiin sekä kvalitatiivisen että kvantitatiivisen tutkimuksen ominaisuuksia. Suppeasta otannasta huolimatta, tutkimus tuotti hyödyllista tietoa verkkomainosten esto-ohjelmien käytöstä yleisesti ja kuluttajien asenteista niitä kohtaan. Tutkimus vahvistaa aikaisempaa käsitystä siitä, että kuluttajat ovat tietoisia verkkomainosten esto-ohjelmien olemassa olosta, ja moni kuluttaja on myös kiinnostunut niiden hyödyntämisestä. Tutkimus myös viittaa siihen, että monet kuluttajista, jotka eivät ole tietoisia verkkomainosten esto-ohjelmien olemassa olosta, olisivat kiinnostuneita käyttämään niitä, jos he tietäisivät näiden ohjelmien olemassaolosta. Syyt verkkomainosten esto-ohjelmien käytölle voivat johtua instrumentaalisista syistä, kuten liian värikkäiden värien käyttämisestä tai institutionaalisista syistä. Myönteisiä asenteita mainosten estämistä kohtaan omaavien vastaajien ohella osa vastaajista eivät kuitenkaan olleet kiinnostuneita verkkomainosten esto-ohjelmien käytöstä. Kuluttajien piirissä näyttäisi olevan myös huoli verkkomainonnan estämisen mahdollisesta negatiivisesta vaikutuksista verkon sisällön laatuun ohjelmien suosion kasvaessa. Tulevaisuudessa onkin hyvin mielenkiintoista nähdä kuinka mainosten estäminen vaikuttaa verkkomainonnan ja verkon sisällön kehitykseen.